Pharmacological Effects and Clinical Applications of Shouhui Tongbian Capsules: A Systematic Review - Xi Yan; Na Li; Lei Wang; Peini Sun; Ru Ma; Xu Ren (Journal of Artificial Intelligence and Information, 2026)
Shouhui Tongbian Capsules (SHTB) is a commonly used Chinese patent medicine for treating functional constipation. Recent studies have shown that its effects go beyond relieving constipation, with potential benefits in improving heart failure, reducing obesity, repairing intestinal injury, and slowing atherosclerosis. This review systematically summarizes 25 studies published between 2020 and 2026, covering clinical trials, pharmacological mechanisms, gut microbiota, and chemical composition. The main topics include: (1) clinical efficacy and safety; (2) molecular pathways such as calcium homeostasis, TGF-β/BMP/Smad, and STAT3/c-Myc; (3) gut microbiota regulation as a core mechanism; (4) chemical composition and quality control; and (5) potential uses beyond constipation. Current evidence suggests that SHTB exerts multi-target synergistic effects by restoring gut microbiota balance, protecting the intestinal barrier, and reducing inflammation. Clinical data support its good safety profile with low adverse reaction rates. Future large-scale, multicenter randomized controlled trials are needed to confirm its value in new indications and to further clarify the relationship between its active components and therapeutic targets.